2021
DOI: 10.1161/strokeaha.120.030565
|View full text |Cite|
|
Sign up to set email alerts
|

Hemostatic Efficacy and Anti-FXa (Factor Xa) Reversal With Andexanet Alfa in Intracranial Hemorrhage: ANNEXA-4 Substudy

Abstract: Background and Purpose: Andexanet alfa is a recombinant modified human FXa (factor Xa) developed to reverse FXa inhibition from anticoagulants. Hemostatic efficacy and reversal of anti-FXa activity with andexanet were assessed in patients from the ANNEXA-4 study (Andexanet Alfa, a Novel Antidote to the Anticoagulation Effects of FXa Inhibitors) with intracranial hemorrhage (ICrH). Methods: ANNEXA-4 was a single-arm study evaluating andexanet in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
1
45
0
1
Order By: Relevance
“…The current retrospective, single-center, observational study included 46 patients with an acute FXa-inhibitor-associated, non-traumatic ICH and evaluated efficacy and safety of reversal the FXa inhibitors with andexanet alfa compared to usual care. In addition to the registration study and some other retrospective studies, there is little experience with AA till today [ 9 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current retrospective, single-center, observational study included 46 patients with an acute FXa-inhibitor-associated, non-traumatic ICH and evaluated efficacy and safety of reversal the FXa inhibitors with andexanet alfa compared to usual care. In addition to the registration study and some other retrospective studies, there is little experience with AA till today [ 9 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma volume was measured on MRI or CT scans. The Tensor Imaging and Fiber Tracking (TIFT) software was used for processing of the imaging data [ 23 , 24 , 25 ]. MRI or CT scans were transformed into a 3-dimensional isotropic grid with a size resolution of 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In the ANNEXA-4 study, in patients with acute major bleeding associated with the use of a FXa inhibitor (including enoxaparin), treatment with andexanet alfa markedly reduced anti-FXa activity, and 82% of patients had excellent or good hemostatic efficacy at 12 h [101]. The ANNEXA-4 sub-study results, evaluating the hemostatic efficacy of andexanet alfa in ICH secondary to anti-FXa, reported a reduced anti-FXa activity in FXa inhibitor-treated patients with ICH, with a high rate of hemostatic efficacy [102]. Andexanet alfa has been recently approved by the US Food and Drug Administration, but some issues slow down its widespread use, such as its brief half-life, poor correlation between in vitro activity and clinical efficacy, and finally, regarding its safety profile, given the in vitro effects and clinical thrombosis rates of up to 18% in early studies [103].…”
Section: Secondary Prevention Of Ischemic Strokementioning
confidence: 99%
“…183 Subgroup analyses showed that a high rate of effective hemostasis post-andexanet was achieved in patients with major GIB or ICH while on apixaban or rivaroxaban. 182,184 Another sub-study of ANNEXA-4 looked at the effect of andexanet on TGT in patients with MBE treated with DOACs. 185 Andexanet bolus increased ETP, which was maintained during infusion up to 18 hours.…”
Section: Specific Antidotesmentioning
confidence: 99%